Part-Time Farming, Diseases and Pest Control Delay and Its External Influence on Pesticide Use in China’s Rice Production - Fang, Chenliang; Xu, Yongqin; Ji, Yueqing (Frontiers in Environmental Science, 2022)
The highly intensive use of pesticide is a big threat to environmental sustainability in China. This study explains the increase of rice pesticide use in China’s rapid urbanization process from the perspective of changes in the delay of pest control. Based on multi-stage random sampling, 20 villages of five counties in central Jiangsu were selected, and the production data of 430 paddy fields were surveyed. Logit model results show that living outside village of agricultural labors will increase the probability of delay in control of diseases and pest, while the increase of farm size and the development of outsourcing services and public monitoring and forecasting services will help reduce the probability of delay. The OLS model results show that the delay in rice diseases and pest control has negative externalities. The delays of other farmers in the village will significantly increase the frequency of pesticide use. These results highlight important policy implications for the development of large-scale farming to substitute part-time farming and the development of diseases and pest control services.